Monocyte CD64 expression as a novel biomarker for the disease activity of systemic lupus erythematosus. (September 2015) - Kikuchi-Taura, A; Yura, A; Tsuji, S; Ohshima, S; Kitatoube, A; Shimizu, T; Nii, T; Katayama, M; Teshigawara, S; Yoshimura, M; Kudo-Tanaka, E; Harada, Y; et al.
Objective: Interferon alpha (IFN-α) is a key cytokine associated with systemic lupus erythematosus (SLE). IFN-α induces the expression of CD64 on monocytes (mCD64). Although enhanced mCD64 expression has been reported in patients with SLE, it has never been assessed quantitatively. The aim of this study was to investigate whether or not mCD64 expression correlates with SLE disease activity. Methods: The mCD64 expression levels were assessed quantitatively in 40 patients with active or inactive SLE by using flow cytometry. The mCD64 expression levels were subsequently compared with the SLE disease activity index (SLEDAI) and levels of existing SLE activity biomarkers, such as anti-DNA antibody, complements, and so on. Results: The mCD64 expression was significantly higher in active disease than in inactive disease SLE (median molecules/cell, interquartile range: 34, 648, 8174–24, 932 and 20, 865, 6357–21, 503, respectively; p  < 0.001). The levels of mCD64 expression strongly correlated with SLEDAI ( r  = 0.68, p  < 0.001). Conclusion: The mCD64 expression is a simple and useful biomarker for evaluating disease activity in patients with SLE.